Synthesis of Some New Chlorostituted Pyrazolines and Their Curative Effect on Induced Hepatotoxicity in Albino Rat - V. Parhate, Vandana; Maurya, M.R.; Deshmukh, M.S.; Rajput, P.R.; Kulkarni, K.M. (Asian Journal of Chemistry, 2010)
Chlorosubstituted 4-aroyl-Δ2-pyrazolines (2a-d) were synthesized by condensing chlorosubstituted 3-aroylflavanones (1a-d) with phenylhydrazine hydrochloride in DMSO containing a little piperidine and assayed these compounds (2a-d) on cythion induced activities in albino rats with special reference to blood serum (VLDL, LDL and HDL) hepatotoxicity. The effects of intraperitonial administration of 4-aroyl-Δ2-pyrazolines (100mg/kg body wt.) were studied on cythion induced blood serum hepatotoxicity. The blood serum VLDL, LDL and HDL were estimated in order to assess the liver functions by established procedures. Biochemical observations were supplemented with histological examination of liver section. It is evident from the results that the levels of serum lipoproteins were more altered in cythion treated animals than controls. There was small but significant decrease in the concentration of total serum lipids which may be largely due to the reduction of the total lipid concentration in the VLDL, LDL and HDL. However, the altered lipoprotein concentration levels were restored to almost normalcy in 4-aroyl-Δ2-pyrazolines treated animals.